Calprotectin and Receptor for Advanced Glycation End Products as a Potential Biomarker in Abdominal Aortic Aneurysm - Willy Hauzer (Journal of Clinical Medicine, 2020)
Experiments conducted in recent years on animals and research works worldwide show a linkage between calprotectin and occurrence and development of the abdominal aortic aneurysm (AAA). Additionally, a correlation between the level of the receptor for advanced glycation end products (RAGE) and the diameter of the abdominal aorta was found. The purpose of this study was to investigate whether calprotectin and the RAGE plasma level may be a biomarker of human AAA occurrence. We determined two groups of research participants: a group of 32 patients aged 53–88 undergoing primary endovascular aneurysm repair and a control group of 43 volunteers aged 59–82 without the AAA. All the patients from the study group had their blood samples drawn in order to determine the level of calprotectin and RAGE in plasma. The second follow-up examination was carried out after three months. The concentration of calprotectin and RAGE in plasma was determined with the use of the immunoenzymatic method (ELISA). The study showed that patients with the AAA had significantly higher mean calprotectin and RAGE plasma levels (p = 0.0001 and p = 0.0002, respectively) as compared to the control group. After the AAA repair operations, the level of concentration of the calprotectin decreased significantly (p = 0.0002). So far, no studies on the connection between the increase of the calprotectin and RAGE in the patient’s plasma with the AAA have been published. Calprotectin may be a promising biomarker related to the occurrence of AAA. Larger studies are needed to fully elucidate and confirm the role of calprotectin in the development and progression of the aneurysm.